Short Communication: Limited Anti-HIV-1 Activity of Maraviroc in Mucosal Tissues - Fletcher,P; Herrera,C; Armanasco,N; Nuttall,J; Shattock,RJ (AIDS Research and Human Retroviruses, 2016)
The potential of maraviroc (MVC), a small-molecule CCR5 antagonist, as a candidate to prevent HIV-1 sexual transmission by oral or topical dosing has not yet been completely established. Using relevant cellular and mucosal tissue explant models, we show partial antiviral activity of MVC when tested in multiple preclinical dosing strategies.